PROTOTIPE KECEPATAN PENUNJUK ARAH DAN PENGUKUR ANGIN BERBASIS MIKROKONTROLER - , IMAM NURHADI PRABOWO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The wind is one of the main components of weather, therefore the wind is often become an interesting research subject especially focus on its speed. The purpose of this research is to apply optocoupler sensor for detecting wind speed and direction. Optocoupler sensor is used to read the perforated disc which connected with three wind catcher. The data of wind speed and direction are obtained from digital calculation of a rotating perforated disc. Every wind gusts, the holey mechanical disc will rotate and cause changes in the sensor optocoupler logic. The logic changes are then processed by a microcontroller into the data of wind speed and direction. This monitoring tool use optocoupler sensor, microcontroller ATmega8 as processor, LM35 as temperature gauges, TLP and RLP 433 module as transmitter and receiver data. Afterwards the measurement results will be displayed in the computer as unit viewer. Based on the observation and calculation, the testing of hardware shows wind direction error is 1.5 degrees, wind speed error at 0.27 km/hour, and temperature error at 0.7 degree. The distribution data obtained from the observations indicate that the data collected from this tool fit with the regression line, it can be interpreted that the data from observational identic with the data from reference tool, or can be concluded that this tool has a high precision.